(untitled) (Research, Society and Development, 2021)
This study aims to analyze the experiences of subjects who live with diabetes and who participated in a group with defined strategies, in relation to disease control and exercise of personal autonomy. This is a participatory study, with a qualitative approach, supported by reflexivity, where the meetings held gave rise to narratives that were organized in thematic axes and analyzed. The work showed that the group assumes the characteristic of a support network, and a facilitating agent for living with the syndrome, where the premise of exchanging experiences contributes significantly to the process of transforming the other, reflecting on the process of co-construction of personal autonomy, and consequently improving the quality of life of the subjects involved. It can be concluded that group practices as a health promotion device, they enable a positive impact on people’s quality of life, development of autonomy and self-care.